The Incidence and Wage Penalty of Overqualification: The Case of Egypt - Ali Fakih; Zeina Lizzaik (Institute of Labor Economics (IZA), 2024)
The phenomenon of overqualification is becoming increasingly common across many countries. In this research study, the main objective is to examine factors that determine overqualification, the impact of overqualification on wages, and the earning differences between genders in the case of Egypt. We use a cross-sectional micro-level dataset taken from the Egyptian Labor Force Survey (LFS) conducted by the Economic Research Forum (ERF). We employ a probit model to capture factors determining overqualification. The empirical results reveal that different sociodemographic, economic sector, and job-related factors determine overqualification. Moreover, we apply different matching techniques, radius matching, nearest-neighbor matching, and a weighting method, inverse probability weighting (IPW) to estimate the causal impact of overqualification on wage earnings. The result shows that overqualification affects the hourly wage earnings negatively. For further investigation, we estimate our regression by gender. The coefficients are negative for both genders, with a higher magnitude among females, revealing that overqualified females face higher wage penalties than overqualified males. The paper provides policy recommendations for both the Egyptian educational system and the job market to mitigate overqualification in the country.
Keywords: I21; J23; J31; 330; overqualification; wage penalty; matching techniques; Egypt